Chemical Product Technology - Murzin, Dmitry Yu (De Gruyter Textbook, 2018)
Chemical Product Technology focuses on materials chemistry and introduces industrial manufacturing technologies for different product types. The author presents a full cycle of product development for the materials that are used in everyday live, such as cosmetics, dyes, drugs, papers, textiles, agrochemicals, etc., starting from product selection and up to setup of manufacturing process.